1993
DOI: 10.1007/bf00357632
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit recruitment during prolonged isometric contractions

Abstract: Motor unit recruitment patterns were studied during prolonged isometric contraction using fine wire electrodes. Single motor unit potentials were recorded from the brachial biceps muscle of eight male subjects, during isometric endurance experiments conducted at relative workloads corresponding to 10% and 40% of maximal voluntary contraction (MVC), respectively. The recordings from the 10% MVC experiment demonstrated a characteristic time-dependent recruitment. As the contraction progressed both the mean numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 22 publications
3
135
0
5
Order By: Relevance
“…By this it is meant that motor units alternate their activity in a cyclical fashion, such that substitution of one motor unit for another would be followed by back-substitution of the original unit. Although this concept is often mentioned within the clinical community, it has been reported by only a few researchers (Fallentin et al 1993;Sjøgaard et al 1986), and these reports have generated more controversy than conviction. Person (1974), Kato et al (1981), and Fallentin et al (1993) among others describe recruitment and silencing of motor units during a contraction, yet none of their studies provides evidence of constant joint torque or muscle force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By this it is meant that motor units alternate their activity in a cyclical fashion, such that substitution of one motor unit for another would be followed by back-substitution of the original unit. Although this concept is often mentioned within the clinical community, it has been reported by only a few researchers (Fallentin et al 1993;Sjøgaard et al 1986), and these reports have generated more controversy than conviction. Person (1974), Kato et al (1981), and Fallentin et al (1993) among others describe recruitment and silencing of motor units during a contraction, yet none of their studies provides evidence of constant joint torque or muscle force.…”
Section: Introductionmentioning
confidence: 99%
“…Although this concept is often mentioned within the clinical community, it has been reported by only a few researchers (Fallentin et al 1993;Sjøgaard et al 1986), and these reports have generated more controversy than conviction. Person (1974), Kato et al (1981), and Fallentin et al (1993) among others describe recruitment and silencing of motor units during a contraction, yet none of their studies provides evidence of constant joint torque or muscle force. De Forrest (1973) andDe Luca et al (1982) found no derecruitment during constantforce isometric contractions of moderate duration at different force levels.…”
Section: Introductionmentioning
confidence: 99%
“…If, during a submaximal constant force contraction, active MUs fatigue and additional ones become recruited, a decrease of the superimposed twitch must occur, indicating an increased excitatory drive to the a-motoneuron pool. The idea of a progressive recruitment of new, unfatigued MUs is primarily based on data from single MU recordings (Moritani et al 1986;Fallentin, J0rgensen & Simonsen, 1993) and on the finding of a time-dependent increase in EMG amplitude (e.g. Edwards & Lippold, 1956;BiglandRitchie et al 1986a;Krogh-Lund & J0rgensen, 1991;L6scher, Cresswell & Thorstensson, 1994).…”
mentioning
confidence: 99%
“…Regarding activity of muscle subvolumes, dynamic reorganisation of the muscle activity within the muscle during sustained contractions has been described [Holtermann et al, 2010[Holtermann et al, , 2008. Moreover, it has been reported that an EMG increase is related with the number of newly recruited motor units during sustained low-level contractions [Fallentin et al, 1993], supporting the stronger impact on force variability by additional motor unit recruitment [Contessa et al, 2009].…”
Section: Spatial Redistribution Of Muscle Activitymentioning
confidence: 96%